Novel color-changing transparent wood material and preparation method thereof

By using a six-membered spirocyclic rhodamine photochromic fluorescent dye with urea-containing structure in transparent wood materials and grafting with bridge molecules, the problem of dye peeling is solved, efficient bonding between dye and cellulose is achieved, and the stability and weather resistance of the material are enhanced.

CN120080395APending Publication Date: 2025-06-03LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510488873.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

When the existing transparent wood materials are bonded through covalent bonds with wood cellulose, the covalent bonds are not firm, causing the dye to fall off easily and affect the stability of the material.

Method used

A six-membered spirocyclic rhodamine photochromic fluorescent dye with urea-containing structure is used and grafted onto a transparent wood material through polyethylene glycol diisocyanate NCO-PEG-NCO, which uses bridge molecules to enhance the bonding force between the dye and cellulose and enhance the stability of the material.

Benefits of technology

It achieves efficient bonding between dyes and cellulose, enhances the stability and weather resistance of color-changing transparent wood materials, and improves the combination of dyes and lignin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005364949380000061
    Figure BDA0005364949380000061
  • Figure HDA0005364949390000011
    Figure HDA0005364949390000011
  • Figure HDA0005364949390000012
    Figure HDA0005364949390000012
Patent Text Reader

Abstract

The invention relates to the field of chemical engineering and environment-friendly materials, and discloses a color-changing transparent wood material and a preparation method thereof. The invention provides a color-changing type transparent wood material for the first time. The color-changing type transparent wood material comprises a transparent wood material base body, bridge intermolecules grafted on lignocellulose of the transparent wood material base body and a photochromic type dye, wherein the dye is a rhodamine derivative. By selecting proper bridging molecules NCO-PEG-NCO and through the hydrophilicity of the bridging molecules, the bonding force between the dye and cellulose is improved, the color change stability of the dye is enhanced, and the combination of the dye and lignin is improved and stabilized. The method comprises the following specific steps: preparing a transparent wood material; the preparation method comprises the following steps: soaking a transparent wood material in a DMF (Dimethyl Formamide) solution, heating, keeping the temperature at 60 DEG C, adding a photochromic rhodamine dye containing a urea structure, reacting for 20 minutes, washing, and soaking in deionized water containing polyethylene glycol diisocyanate to obtain the transparent wood material grafted with the rhodamine dye.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new environmentally friendly materials, and specifically relates to a color-changing transparent wood material and a preparation method thereof. Background Art

[0002] In the long exploration of materials science, the birth of new materials is often accompanied by the unremitting efforts and wisdom of countless researchers. Transparent wood materials are an outstanding representative. In 1992, German botanist Siegfried Fink took a groundbreaking step. He delved deeply into the mysteries of plant cells and successfully removed the pigments in plant cells through a unique bleaching technique, thus creating transparent wood materials, laying the foundation for the research in this new material field and attracting researchers around the world to join the research wave of transparent wood materials.

[0003] In recent years, research teams such as Liangbing Hu from the University of Maryland and Lars Berglund from the KTH Royal Institute of Technology in Sweden have achieved remarkable results in the field of transparent wood materials. With their outstanding innovative spirit, Liangbing Hu's team invented a more environmentally friendly and efficient preparation method. While fading the color of lignin, its vital supporting structure is intact. Studies have found that the strength of the treated transparent wood material is 6 times higher than that of the original wood, and compared with glass, it shows better toughness. This breakthrough has made transparent wood materials stand out in the field of materials science and has also triggered people's endless imagination about its wide application.

[0004] As material science develops rapidly, the research on transparent wood materials is advancing like a galloping train. In particular, the major breakthroughs in optical, mechanical and thermal properties have made it a star material with great potential and wide application prospects.

[0005] In terms of optical performance, through advanced technical processing, wood composite materials have successfully achieved a high degree of transparency, and its light transmittance can reach 80%-90%, which is comparable to ordinary glass. What is more unique is that it also has light scattering properties, which makes it like a duck in water in diffuse light application scenarios. For example, applying it to the field of lighting can not only provide people with a clear and open field of vision, allowing a panoramic view of the beautiful scenery outside the window, but also introduce sufficient natural light to create a bright and comfortable indoor environment. Not only that, researchers have also found that by using different fillers, the light transmittance of transparent wood materials can be flexibly adjusted to meet the diverse needs in different scenarios.

[0006] In terms of mechanical properties, the transparent wood material retains the original fiber structure of wood, which gives it the dual advantages of high strength and high toughness. Compared with ordinary glass, it is not easy to break, and its safety is greatly improved. In daily use and some special scenarios, it greatly reduces the safety hazards caused by material breakage. At the same time, this fiber structure also makes it have strong corrosion resistance and anti-aging properties, effectively extending the service life of the material and reducing the waste of resources and cost increase caused by frequent material replacement.

[0007] In terms of thermal performance, transparent wood materials have low thermal conductivity, which makes them more energy-efficient than glass and an ideal choice for building windows and insulation materials. For example, by filling phase change materials (such as polyethylene glycol), researchers have successfully given transparent wood materials the ability to store and release heat. During the day, it can absorb and store excess heat to prevent the indoor temperature from being too high; at night or when the temperature is lower, it can release the stored heat to maintain indoor warmth and comfort, effectively reducing the energy consumption of buildings and making a positive contribution to energy conservation and emission reduction.

[0008] In the field of environmental protection, transparent wood materials also show incomparable advantages. It uses natural wood as raw material, which is a renewable resource with a wide range of sources and is sustainable and inexhaustible. Discarded transparent wood materials can be naturally degraded and will not cause any burden to the environment, which perfectly fits the concept of green development in today's society. In addition, during the production process, the emission of volatile organic compounds of transparent wood materials is extremely low, which plays a vital role in reducing indoor air pollution and creating a healthy indoor environment.

[0009] It is worth mentioning that color-changing dyes can also be used to give transparent wood materials a unique anti-counterfeiting function. This innovative application has opened up new application directions for transparent wood materials in some fields with extremely high anti-counterfeiting requirements, such as high-end product packaging and important document protection. However, when the dye is covalently bonded to wood cellulose, the covalent bond is often not strong, and the dye is prone to fall off, seriously affecting its stability. In order to enhance the application scenarios of color-changing transparent wood materials, bridging molecules are introduced during the dyeing process to achieve efficient bonding between the dye and cellulose to enhance its stability. Summary of the invention

[0010] The purpose of the present invention is to solve the existing stability problem in the above background technology. Therefore, the present invention proposes a method for preparing a color-changing transparent wood material with good stability.

[0011] The present invention first proposes a preparation method of a color-changing transparent wood material by grafting a six-membered spiro-rhodamine photochromic fluorescent dye containing a urea structure onto transparent wood material through polyethylene glycol diisocyanate NCO-PEG-NCO, obtaining a color-changing transparent wood material. By selecting a suitable bridging molecule NCO-PEG-NCO, through the hydrophilicity of the bridging molecule, the bonding force between the dye and cellulose is enhanced, its color-changing stability is improved, and the combination of the stable dye and lignin is improved.

[0012] To achieve the above object, the technical solution of the present invention is as follows. A color-changing transparent wood material includes a transparent wood material matrix, a bridging molecule grafted onto the wood cellulose of the transparent wood material matrix, and a photochromic dye, and the dye is a rhodamine derivative.

[0013] Further, in the above color-changing transparent wood material, the bridging molecule is polyethylene glycol diisocyanate.

[0014] Further, in the above color-changing transparent wood material, the photochromic dye is a rhodamine-based color-changing dye.

[0015] The preparation method of the above color-changing transparent wood material includes the following steps:

[0016] 1) Preparation of transparent wood material: Immerse the wood material in a delignification solution, adjust the pH to acidic, perform a water bath, and change the delignification solution every 6 hours until the wood material turns white. After washing, store it in an organic solvent, and after drying, immerse it in an epoxy resin filling solution. Use the vacuum-assisted impregnation method to make the epoxy resin filling solution fully penetrate the wood pores. After taking it out, let it stand and polish to obtain a transparent wood material filled with epoxy resin.

[0017] 2) Color-changing transparent wood material: Put the transparent wood material obtained in step 1) into a DMF solution of NCO-PEG-NCO, soak it at 60 °C, prepare a rhodamine DMF solution, heat it to 60 °C, and immerse the transparent wood material reacted with NCO-PEG-NCO into the rhodamine DMF solution, soak and wash to obtain a color-changing transparent wood material.

[0018] Further, in the preparation method of the above color-changing transparent wood material, in step 1), the wooden material is the tangential section or longitudinal section of wood such as basswood.

[0019] Further, in the preparation method of the above color-changing transparent wood material, the preparation sequence can also be changed. By using the bridging molecule to quickly react and bond with the hydroxyl groups on cellulose, an isocyanate group-containing group is introduced at a specific part of the transparent wood material, which is convenient for subsequent bonding with the color-changing dye.

[0020] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 1), the delignification solution is a mixed solution of 1% sodium chlorite solution, ozone and glacial acetic acid.

[0021] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 1), adjusting the pH to acidic means adjusting the pH to be between 4 and 5.

[0022] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 1), the water bath is a water bath at 80 °C for more than 12 h.

[0023] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 1), the epoxy resin filling solution is obtained by dissolving epoxy resin in acetone or other organic solvents.

[0024] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 1), the vacuum-assisted impregnation method has a vacuum degree of 0.1 MPa. Under the action of vacuum, the air in the wood pores is pumped out to form a negative pressure, and the filling solution fully penetrates into the pore structure of the wood under the action of the pressure difference.

[0025] Furthermore, in the preparation method of the above-mentioned color-changing transparent wood material, in step 2), the concentration of rhodamine in the rhodamine DMF solution is 2 mg / mL.

[0026] Furthermore, for the preparation method of the above-mentioned color-changing transparent wood material, the rhodamine derivative is a six-membered spirocyclic rhodamine photochromic fluorescent dye containing a urea structure, and the preparation method is as described in Patent ZL2021105102143.

[0027] Advantages of the present invention: The present invention uses a six-membered spirocyclic rhodamine photochromic fluorescent dye containing a urea structure grafted onto the transparent wood material, making it have photochromic properties, good stability and strong weather resistance. At the same time, the present invention uses ozone to enhance the delignification ability of the sodium chlorite solution, which has the advantages of simple and convenient operation, renewable materials, environmental protection, and the obtained transparent wood material has relatively high toughness, high strength, and high transparency. Description of the Drawings

[0028] Figure 1 It shows the effect of the wood material in Example 1 without being soaked in the delignification solution.

[0029] Figure 2 It shows the effect of the wood material in Example 1 after being soaked for 3.0 hours.

[0030] Figure 3 It shows the final obtained transparent wood material in Example 1.

[0031] Figure 4 To achieve the photochromic effect of the color-changing transparent wood material obtained in Example 2.

[0032] Figure 5 For the delignified lignocellulose framework material prepared in Example 3.

[0033] Figure 6 In the order from left to right are the photochromic effects of the color-changing delignified material in Example 3 after being dyed and placed for one day, ten days, and fifteen days.

[0034] Figure 7 For the chemical formula of the novel photochromic fluorescent dye of hexa-spiro-rhodamine containing urea structure in Examples 2 and 3.

[0035] Figure 8 For the chemical principle of grafting the novel photochromic fluorescent dye of hexa-spiro-rhodamine containing urea structure in Example 2 onto the cellulose framework. Detailed implementation method

[0036] Example 1: Preparation of transparent wood material

[0037] Select the tangential section of Tilia wood with a length of 5 cm, a width of 5 cm, and a thickness of 0.38 mm as the raw material, as Figure 1 shown. Immerse the wood chips in a 1% sodium chlorite solution and ozone in an acetic acid buffer solution. The pH of the mixed solution needs to be adjusted to 4.6, and heat to maintain an 80 °C water bath for more than 12 hours. Figure 2 For the effect of the wood material immersed for 3 hours. Replace the delignification solution every 6 hours to ensure the delignification efficiency. Repeat the delignification process until the wood chips turn white. Wash the delignified wood with a 1:1 solution of water / ethanol several times to obtain delignified wood chips, which can be stored in organic solvents such as propanol. Before filling with the organic polymer, dry the delignified wood chips at 60 °C for more than 12 hours to ensure they are completely dry. Dissolve the epoxy resin in acetone or other organic solvents to prepare a filling solution to form a low-viscosity solution. Immerse the wood in the solution, and use the vacuum-assisted impregnation method (vacuum degree 0.1 MPa) to make the solution fully penetrate the wood pores. Take out the wood and let it stand at room temperature for 12 hours to allow the solvent to volatilize. Heat the filled wood at 80 - 100 °C for 2 - 4 hours to cure the polymer. After cooling to room temperature, sand the surface to remove the excess polymer. A transparent wood material with a lignocellulose framework and an epoxy resin filler is obtained. Figure 3 For the finally obtained transparent wood material.

[0038] Example 2: Preparation of color-changing transparent wood material

[0039] The hydroxyl groups of lignocellulose are linked to rhodamine through the isocyanate groups of NCO-PEG-NCO, and stable amide bonds are formed through reaction to attach rhodamine to the cellulose molecular chain. Figure 7 It is the chemical formula of a novel photochromic fluorescent dye of hexaspirolactam rhodamine containing a urea structure. Figure 8 It is the linking chemical principle. The prepared transparent wood material is put into a DMF solution of 0.08 g / mL NCO-PEG-NCO, stirred and soaked at 60 °C for 8 hours to allow NCO-PEG-NCO to react with cellulose. Then, a 2 mg / mL rhodamine DMF solution is prepared, heated to 60 °C, and the wood chips reacted with NCO-PEG-NCO are immersed, and the temperature is maintained by heating for 20 minutes. After the reaction, it is washed repeatedly with deionized water and immersed therein to obtain a color-changing transparent wood material with a controllable dyeing range. Figure 4 It is the photochromic effect. Figure 6 It is the photochromic effect of the transparent wood material after being dyed and placed for one day, ten days, and fifteen days.

[0040] Example 3 Preparation of color-changing delignified framework

[0041] The preparation operation can be adjusted. First, a color-changing cellulose framework is prepared, and then it is filled with epoxy resin to make a color-changing transparent wood material.

[0042] In this experiment, the tangential section of Tilia wood with a size of 5 cm in length, 5 cm in width, and 0.38 mm in thickness is selected as the raw material. First, a delignifying solution is prepared. Sodium chlorite is added to an acetic acid buffer solution to make its concentration reach 1%, and ozone is introduced, and the pH value of the mixed solution is adjusted to 4.6 with the corresponding reagent.

[0043] After the wood chips are completely immersed in the above delignifying solution, they are placed in a water bath environment at 80 °C for heat treatment, and the treatment time needs to be more than 12 hours. To ensure the delignification efficiency, the delignifying solution needs to be replaced every 6 hours. This delignification process is continuously repeated until the wood chips turn white.

[0044] When the wood chips turn white, it indicates that the delignification is basically completed. Subsequently, the delignified wood is washed repeatedly with a mixed solution of water and ethanol with a volume ratio of 1:1 to obtain a delignified cellulose framework. Figure 5 It is the delignified cellulose framework. If the next experiment is not carried out immediately, the delignified cellulose framework can be stored in an organic solvent such as propanol.

[0045] Next, a chemical grafting reaction is carried out. The isocyanate groups of NCO-PEG-NCO are used to achieve the connection between the hydroxyl groups of lignocellulose and rhodamine. The reaction between the two can form stable amide bonds, thus successfully grafting rhodamine onto the cellulose molecular chain. The specific operation is as follows. First, put the prepared delignified cellulose framework into a DMF solution of HDI with a concentration of 0.08 g / mL, and stir and soak it at a proper stirring speed for 8 hours in an environment of 60 degrees Celsius, so that NCO-PEG-NCO fully reacts with cellulose.

[0046] Then, prepare a rhodamine DMF solution with a concentration of 2 mg / mL and heat it to 60 degrees Celsius. Immerse the wood chips after reacting with NCO-PEG-NCO in this rhodamine DMF solution, and also keep the heating state at 60 degrees Celsius and soak for 20 minutes. After the reaction is completed, wash the wood chips with deionized water multiple times, and then immerse them in deionized water to finally obtain a fully dyed color-changing delignified cellulose framework.

[0047] Example 4 Filling the resin material in the color-changing delignified cellulose framework

[0048] Before filling the delignified wood chips with an organic polymer, pretreatment is required. Place the delignified wood chips in a drying environment of 60 degrees Celsius and continue drying for more than 12 hours to ensure that the internal moisture of the wood chips is completely evaporated and reaches a completely dry state.

[0049] Next, prepare the solution for filling. Select epoxy resin as the filling material and dissolve it in acetone or other organic solvents with good solubility. During the dissolution process, promote dissolution by stirring and other means to make the epoxy resin evenly dispersed, thereby forming a solution with low viscosity. This is beneficial for the solution to better penetrate into the wood pores during the subsequent filling process.

[0050] The vacuum-assisted impregnation method is used to achieve the filling of the solution into the wood. Immerse the completely dry delignified wood chips completely in the prepared filling solution, and then place them in a vacuum environment with a set vacuum degree of 0.1 MPa. Under the action of vacuum, the air in the wood pores is pumped out to form a negative pressure, and the filling solution penetrates into the pore structure of the wood under the action of the pressure difference to ensure that every pore is filled with the solution.

[0051] After filling is completed, take out the wood from the solution and place it at room temperature for 12 hours. During this period, the organic solvents in the solution will gradually volatilize, increasing the concentration of epoxy resin in the wood pores.

[0052] Subsequently, to cure and mold the epoxy resin, the filled wood was placed in a heating device, and the temperature was controlled in the range of 80 - 100 °C and heated continuously for 2 - 4 hours. Within this temperature range, cross-linking reactions occurred between epoxy resin molecules, gradually changing from a liquid state to a solid state, tightly filling the pores of the wood and forming a tight bond with the lignocellulose framework.

[0053] After the heating and curing were completed, the wood was allowed to cool naturally to room temperature. At this time, there may be excess polymer residues on the wood surface, and the surface was carefully polished with sandpaper. During the polishing process, control the strength and direction to remove the excess epoxy resin on the surface completely, making the wood surface flat and smooth.

[0054] Example 5 Photochromic Property Test

[0055] The samples were irradiated with UV at a wavelength of 365 nm and fluorescent lamps for color change and recovery, and the color difference was detected with a colorimeter. The samples were irradiated for several cycles to test their cyclic color change ability. Laminated films with different patterns were formed to cover the surface of the samples. Further, under UV irradiation, the integrity of the pattern display, as well as the prominence of the laminated and color-changing areas, were observed.

[0056] The following color difference calculation formula was used:

[0057]

[0058] Where ΔL, △a, and △b represent the differences between two color data points on the L, a, and b axes respectively. In the CIELAB color space (used for color measurement in this study), the L (lightness) axis represents black and white (0 represents black, 100 represents white), the a (red - green) axis represents red and green (positive values for red, negative values for green, 0 is the neutral color), and the b (yellow - blue) axis represents yellow and blue (positive values for yellow, negative values for blue, 0 is the neutral color).

[0059] Under the irradiation of UV at a wavelength of 365 nm and fluorescent lamps, the color - changing transparent wood materials can turn pink, and the color gradually disappears after the irradiation is removed. Due to the ring - opening and ring - closing reactions that occur when the novel photochromic fluorescent dye containing a urea structure in the six - membered spiro - rhodamine is exposed to light and the light is removed, the absorption spectrum shifts, resulting in a color change. At the same time, in the cyclic irradiation test, as the number of cycles increases, the color - changing performance of the color - changing transparent wood materials weakens to a certain extent, but after being placed for 48 hours, their performance partially recovers.

Claims

1. A color-changing transparent wood material, characterized in that: The invention comprises a transparent wood material matrix, a bridge molecule grafted onto the wood cellulose of the transparent wood material matrix, and a photochromic dye, wherein the dye is a rhodamine derivative.

2. A color-changing transparent wood material according to claim 1, characterized in that: The bridge molecule is polyethylene glycol diisocyanate.

3. The color-changing transparent wood material according to claim 1, characterized in that: The photochromic dye is a rhodamine-type photochromic dye.

4. The method for preparing the color-changing transparent wood material according to any one of claims 1 to 3, characterized in that: The steps include: 1) Preparation of transparent wood material: immerse the wood material in a delignification solution, adjust the pH to acidic, conduct a water bath, replace the delignification solution every 6 hours until the wood material turns white, wash and store in an organic solvent, dry and immerse in an epoxy resin filling solution, use a vacuum-assisted impregnation method to allow the epoxy resin filling solution to fully penetrate the wood pores, take out and let stand, and polish to obtain a transparent wood material filled with epoxy resin; 2) Color-changing transparent wood material: the transparent wood material obtained in step 1) is placed in a DMF solution of NCO-PEG-NCO and immersed at 60° C., a rhodamine DMF solution is prepared and heated to 60° C., the transparent wood material reacted with NCO-PEG-NCO is immersed in the rhodamine DMF solution, and the color-changing transparent wood material is obtained by immersing and washing.

5. The method for preparing the color-changing transparent wood material according to claim 4, characterized in that: In step 1), the delignification solution is a mixture of 1% sodium chlorite solution, ozone and glacial acetic acid.

6. The method for preparing a color-changing transparent wood material according to claim 4, characterized in that: In step 1), the step of adjusting the pH to acidic is adjusting the pH to between 4 and 5.

7. The method for preparing a color-changing transparent wood material according to claim 4, characterized in that: In step 1), the water bath is 80° C. for more than 12 hours.

8. The method for preparing a color-changing transparent wood material according to claim 4, characterized in that: In step 1), the epoxy resin filling solution is obtained by dissolving epoxy resin in acetone or other organic solvents.

9. The method for preparing a color-changing transparent wood material according to claim 4, characterized in that: In step 1), the vacuum assisted impregnation method has a vacuum degree of 0.1 MPa. Under the vacuum, the air in the pores of the wood is extracted to form a negative pressure, and the filling solution fully penetrates into the pore structure of the wood under the action of the pressure difference.

10. The method for preparing a color-changing transparent wood material according to claim 4, characterized in that: In step 2), the concentration of rhodamine in the rhodamine DMF solution is 2 mg / mL.